Potential classification of chemical immunologic response based on gene expression profiles. Issue 1 (1st January 2020) - Anderson, Stacey E.; Baur, Rachel; Kashon, Michael; Lukomska, Ewa; Weatherly, Lisa; Shane, Hillary L.
Abstract: Occupational immune diseases are a serious public health burden and are often a result of exposure to low molecular weight (LMW) chemicals. The complete immunological mechanisms driving these responses are not fully understood which has made the classification of chemical allergens difficult. Antimicrobials are a large group of immunologically-diverse LMW agents. In these studies, mice were dermally exposed to representative antimicrobial chemicals (sensitizers: didecyldimethylammonium chloride (DDAC), ortho -phthalaldehyde (OPA), irritants: benzal-konium chloride (BAC), and adjuvant: triclosan (TCS)) and the mRNA expression of cytokines and cellular mediators was evaluated using real-time qPCR in various tissues over a 7-days period. All antimicrobials caused increases in the mRNA expression of the danger signals Tslp (skin), and S100a8 (skin, blood, lung). Expression of the TH 2 cytokine Il4 peaked at different timepoints for the chemicals based on exposure duration. Unique expression profiles were identified for OPA ( Il10 in lymph node, Il4 and Il13 in lung) and TCS ( Tlr4 in skin). Additionally, all chemicals except OPA induced decreased expression of the cellular adhesion molecule Ecad . Overall, the results from these studies suggest that unique gene expression profiles are implicated following dermal exposure to various antimicrobial agents, warranting the need for additional studies. In order to advance the development of preventative and therapeutic strategies to combat immunological disease, underlying mechanisms of antimicrobial-induced immunomodulation must be fully understood. This understanding will aid in the development of more effective methods to screen for chemical toxicity, and may potentially lead to more effective treatment strategies for those suffering from immune diseases.